Development Characteristics and Finite Element Simulation of Fractures in Tight Oil Sandstone Reservoirs of Yanchang Formation in Western Ordos Basin - Wang, Shilin; Li, Hu; Lin, Lifei; Yin, Shuai (Frontiers in Earth Science, 2022)
Structural fractures have a significant control effect on the large-scale accumulation of hydrocarbons in the Yanchang Formation. Previous studies have affirmed the important role of fractures in hydrocarbon accumulations in strongly deformed zones. However, for low-amplitude structural areas, the degree of fracture development is relatively low, and their control on sweet spots of hydrocarbons has not yet formed a unified understanding. In this paper, taking the Upper Triassic Yanchang Formation in the western Ordos Basin as an example, the development characteristics, prediction method, and the distribution of fractures in tight sandstone reservoirs in low-amplitude structural areas have been systematically studied using a large number of cores, thin sections, paleomagnetism, FMI logging, acoustic emission, productivity data and finite element method. The research results showed that the Yanchang Formation in the study area mainly develop high-angle and vertical fractures, which were formed by regional tectonic shearing. Fractures are mainly developed in the fine-grained and ultra-fine-grained sandstones of the distributary channel and estuary bar microfacies, while the fractures in the medium-grained sandstones of the distributary channel and the mudstones of the distributary bay are relatively underdeveloped. The core fractures and micro-fractures of the Yanchang Formation all have the regional distribution characteristics, and the fracture strikes are mainly between NE50° and NE 70°. Moreover, the finite element method was used to predict the fractures in the target layer, and the prediction results are consistent with the actual distribution results of the fractures. The coupling analysis of fractures and tight oil sandstone distribution showed that the existence of fractures provided conditions for the accumulation of hydrocarbons in the Yanchang Formation. The confluence and turning areas of the river channels were repeatedly scoured by river water, and the rocks were brittle and easy to form fractures. The thickness of the fractured sandstone in these areas is usually greater than 0.4 m. Moderately developed fracture zones are prone to form hydrocarbon accumulation "sweet spots", and the fracture indexes of these areas are usually distributed between 0.8 and 1.2. However, when the fracture index exceeds 1.2, over-developed fractures are unfavorable for the accumulation of hydrocarbons.